Analisis Patogenisitas Fusarium solani dan Pengaruhnya terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah - Jayadi, Irfan; Sanuriza, Irna Il; Risfianty, Dwi Kartika; Ihwan, Khaerul; Husain, Pahmi; Dewi, Irma Risvana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Fusarium wilt disease caused by Fusarium sp. is one of the main obstacles in the cultivation of shallots (Allium cepa L.), because it can significantly reduce the quality and quantity of crops. This study aims to test the level of pathogenicity of Fusarium solani and analyze the effect of disease attacks on the growth and yield of shallot plants. The study used a two-factor Complete Random Design (RAL) with 6 treatment combinations and 3 replicas on three varieties of shallots inoculated with Fusarium solani. Growth parameters and disease intensity were analyzed using ANOVA and DMRT test at 5%. The results of the study showed that the fungus Fusarium solani f.sp. Cepae has been shown to have high virulence in shallots, indicated by a short incubation period (3-6 days) and an attack rate of up to 100% in all varieties tested. This pathogenic infection decreases vegetative growth (plant height and number of leaves) as well as yield (fresh and dry weight). The Keta Monca variety shows relatively better resistance than the Bima Brebes and Super Philip varieties, although there is no variety that is completely resistant to Fusarium solani attacks. Fusarium solani infection not only inhibits vegetative growth, but also significantly decreases yields. These findings confirm that Fusarium solani has high pathogenicity and has the potential to be a serious threat in onion cultivation.